STRATEGI KOMUNIKASI PENYULUH AGAMA ISLAM KUA KECAMATAN MADAT, ACEH TIMUR DALAM MENGANTISIPASI PERNIKAHAN DINI - Junaidi (Journal of Contemporary Indonesian Islam, 2024)
This journal explains the communication strategy carried out by the Islamic Religious Counselor of the KUA of Madat District, East Aceh Regency in anticipating early marriage. This research was conducted because seeing the age of early marriage in the KUA of Madat District is not high and high, of course in this case there is a way of communication or delivery of pean carried out by the KUA of Madat District in anticipating early marriage in the region. In compiling this journal, researchers used a type of qualitative research. In collecting data, researchers used three techniques, namely observation, interviews, and documentation. The results showed that: 1) The role of the Islamic Religious Counselor of the KUA of Madat District in anticipating early marriage is: a) As an informative function and as an educative. b) The instructor conducts socialization or or provides understanding to the community about the applicable rules, namely Law No. 16 of 2019 concerning the age of marriage. c) Providing socialization in the form of counseling, be it in the form of discussion forums, recitations, and all forms created by groups. d) The instructor acts as counselor, mentor, there are even instructors at the KUA who act as special for capil and health counseling. 2) Factors causing early marriage in Madat Sub-district include a) Lack of socialization, b) As a result of promiscuity, c) Economic limitations, d) Cultural factors, and e) The influence of social media factors. 3) Communication strategies used by KUA Islamic religious instructors are da'wah communication strategies, unidirectional communication strategies, reciprocal communication strategies. Here more to group communication, in the form of advice and guidance by providing counseling